2006
DOI: 10.1302/0301-620x.88b2.16456
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting fracture healing after intramedullary nailing of the tibial diaphysis for closed and grade I open fractures

Abstract: As there is little information on the factors that influence fracture union following intramedullary nailing of the tibia we retrospectively investigated patient-, injury- and treatment-related factors in 161 patients with closed or grade I open fractures of the tibial diaphysis. The patients were reviewed until clinical and radiological evidence of union at a mean of 13.3 months (4 to 60). Multivariate statistical analysis using a Cox proportional hazards model showed that the risk of failure of union increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 18 publications
3
45
2
3
Order By: Relevance
“…Our findings on displacement are consistent with those of Drosos et al, who found that a post-reduction fracture gap of ≥ 3 mm with a statically locked nail was associated with a significantly longer time to union than a gap of < 3 mm (Drosos et al 2006). The degree of comminution was also significantly associated with healing, and there was a tendency towards slower healing in distal fractures compared to midshaft and proximal fractures.…”
Section: Major Complicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on displacement are consistent with those of Drosos et al, who found that a post-reduction fracture gap of ≥ 3 mm with a statically locked nail was associated with a significantly longer time to union than a gap of < 3 mm (Drosos et al 2006). The degree of comminution was also significantly associated with healing, and there was a tendency towards slower healing in distal fractures compared to midshaft and proximal fractures.…”
Section: Major Complicationssupporting
confidence: 91%
“…Translational displacement has been recognized as a risk factor for delayed union in the treatment of tibial shaft fractures (Helland et al 1996, Audigé 2005, Drosos 2006), but it has received no attention in tibial pilon fractures. Our findings on displacement are consistent with those of Drosos et al, who found that a post-reduction fracture gap of ≥ 3 mm with a statically locked nail was associated with a significantly longer time to union than a gap of < 3 mm (Drosos et al 2006).…”
Section: Major Complicationsmentioning
confidence: 99%
“…We understand that postoperative fracture gap does play an important role in nonunion, and we think that most clinicians do not require 0.006 AO = Arbeitsgemeinschaft für Osteosynthesefragen; GSW = gunshot wound; ASA = American Society of Anesthesiologists; EtOH = ethyl alcohol; WB = weightbearing; WBAT = weightbearing as tolerated. assistance in predicting nonunions among fractures that have sizeable gaps postoperatively [18]. The treatment dilemma that currently exists concerns the fracture with at least some cortical contact postoperatively [19,33].…”
Section: Discussionmentioning
confidence: 99%
“…Too much or too little motion at the fracture site, excessive space between fracture fragments, inadequate fixation, infection, soft tissue interposition, inadequate blood supply, and many other factors can lead to nonunion (Shuler 1996;Rosen 1998;Audige et al, 2005;Drosos et al, 2006). Our patient had not any well-known causes of pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 77%